The effect of a stepped lip piston design on performance and emissions from a high-speed diesel engine. (1st April 2018) - Leach, Felix; Ismail, Riyaz; Davy, Martin; Weall, Adam; Cooper, Brian
Highlights: A stepped lip and standard piston are compared in a high speed diesel engine. An excellent experimental-CFD match is observed and used to understand the results. Previously unobserved slower burn rates are noted for the stepped lip piston. The geometry of the stepped lip explains this variation. Abstract: Understanding engine-out NOx and soot emissions from light-duty diesel engines is vital for improving combustion system design and ultimately for reducing aftertreatment requirements. In this work two piston bowl shapes, a standard re-entrant bowl and a bowl with a stepped lip, are tested experimentally and numerically at two part-load operating points (1500 rpm/6.8 bar net IMEP and 1750 rpm/13.5 bar net IMEP), and four full-load operating points (1500, 2000, 3000, and 4000 rpm). The results show that the stepped lip design consistently increases the 50–90% MFB duration across all operating conditions due to the trapping of the flame in the region of the stepped lip. Use of the stepped bowl allowed injection timing to be advanced at full load, a condition constrained, in this work, by strict limits of cylinder pressure and exhaust temperature. However, despite these changes in combustion behavior engine out emissions were found to be largely insensitive to the bowl shape. No statistical difference in NOx and soot emissions between the two bowl geometries was observed at part load. A minor penalty in NOx emissions, statistically significant at ∼67% CI, is reported for the stepped bowl design at some full load points.